2010
DOI: 10.1371/journal.ppat.1000824
|View full text |Cite
|
Sign up to set email alerts
|

Topology and Organization of the Salmonella typhimurium Type III Secretion Needle Complex Components

Abstract: The correct organization of single subunits of multi-protein machines in a three dimensional context is critical for their functionality. Type III secretion systems (T3SS) are molecular machines with the capacity to deliver bacterial effector proteins into host cells and are fundamental for the biology of many pathogenic or symbiotic bacteria. A central component of T3SSs is the needle complex, a multiprotein structure that mediates the passage of effector proteins through the bacterial envelope. We have used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
165
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(178 citation statements)
references
References 26 publications
12
165
0
1
Order By: Relevance
“…To visualize the needle complex of the type III secretion injectisome of Salmonella enterica serovar Typhimurium (S. Typhimurium) (8) by SMSN, we first constructed a strain expressing PrgH, a component of its inner ring (18) (Fig. 1A and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To visualize the needle complex of the type III secretion injectisome of Salmonella enterica serovar Typhimurium (S. Typhimurium) (8) by SMSN, we first constructed a strain expressing PrgH, a component of its inner ring (18) (Fig. 1A and SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The needle is capped at its end by the tip complex, which is thought to coordinate the activation of the secretion machine upon contact with target cells (9,10). Because the needle complex can be isolated in a manner suitable for single-particle cryo-electron microscopy, its organization at the quasi-atomic level is known (11)(12)(13)(14)(15)(16)(17)(18). Passage of the secreted proteins through the inner membrane requires the export apparatus, which is composed of a group of poly-topic inner membrane proteins located at the center of the needle complex base (19).…”
mentioning
confidence: 99%
“…Although the inner rod has not been unambiguously visualized by electron microscopy, the structural similarity of the building subunits indicates that the inner rod and needle structures are likely to be structurally similar. In fact, the transition between inner rod and needle substructures is not clearly demarcated in low-resolution electron microscopic images (22). Therefore, to investigate the role of InvJ in inner rod assembly we developed an assay that could report on the assembly of this substructure.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, it is likely that just the cup substructure, which is present even in the absence of InvJ (18), is formed by SpaP, SpaQ, and SpaR. Taken together, these results indicate that a subset of the export apparatus components form a defined substructure on the basal face of the NC and may account for yet unassigned density in the NC protein density map (12). Additional studies will be required to localize InvA and SpaS, which are lost from NC preparations generated with the stringent isolation protocol that is required to obtain particles suitable for cryo-electron microscopy.…”
Section: Components Of the Export Apparatus Form A Defined Structurementioning
confidence: 95%
“…The NC is composed of a multiring base (made up in the S. Typhimurium SPI-1 T3SS by the InvG, PrgH, and PrgK proteins), a central inner rod (made up by PrgJ), and a protruding needle-like structure (made up by PrgI), which is traversed by ∼28 Å-wide channel that serves as a conduit for passage of the secreted proteins through the bacterial envelope (6,7). The recent availability of the crystal structures of soluble domains of some of the components of the NC (8)(9)(10), combined with their docking onto the NC protein density map generated by cryo-electron microscopy (7,11), is beginning to provide a high-resolution view of this organelle (12). Previous studies have shown that assembly of the needle complex occurs in an orderly manner, in which the base substructure is assembled first, followed by the assembly of the inner rod and needle substructure (13,14).…”
mentioning
confidence: 99%